2018
DOI: 10.1590/0100-6991e-20181586
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of systemic early postoperative inflammatory response among elderly and non-elderly patients undergoing laparoscopic cholecystectomy

Abstract: Objective: to evaluate and compare the early postoperative period systemic inflammatory response between elderly and non-elderly patients submitted to laparoscopic cholecystectomy, mainly performing a quantitative analysis of interleukin-6 (IL-6), a marker of inflammatory activity systemic. Methods: we compared a series of cases over a period of six months at the Gaffrée and Guinle University Hospital of the Federal University of the State of Rio de Janeiro, involving 60 patients submitted to elective laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These results are in accordance with the previous studies reported for other plants [ 78 , 79 , 80 ]. These phytochemical substances were already proven to possess anti-inflammatory properties [ 81 ]. Among them, terpenes, alkaloids, and phenolic compounds, i.e., flavonoids, lignans, saponins, tannins, and coumarins, are especially prominent [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with the previous studies reported for other plants [ 78 , 79 , 80 ]. These phytochemical substances were already proven to possess anti-inflammatory properties [ 81 ]. Among them, terpenes, alkaloids, and phenolic compounds, i.e., flavonoids, lignans, saponins, tannins, and coumarins, are especially prominent [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, plants have become the first source of substances for the development of new drugs, and a considerable part of the drugs prescribed in the world are derived from them [ 9 , 45 , 46 , 47 ]. Plants contain reservoirs of potential secondary metabolites that are the major sources of drugs, which intensifies the interest of transnational industries in the search for substances obtained from plant sources, particularly since the great majority of species have not been studied chemically or biologically [ 48 ].…”
Section: Plant Use and The Development Of Drugsmentioning
confidence: 99%
“…Substances of plant origin, belonging to the most diverse chemical classes, have already demonstrated proven anti-inflammatory activity [ 9 ]. Among them, alkaloids, terpenes [ 81 , 82 , 83 , 84 ], and phenolic compounds such as tannins, lignans, coumarins, saponins, and especially the flavonoids stand out [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ] ( Figure 1 ).…”
Section: Anti-inflammatory Molecules Of Medicinal Plants and Mechamentioning
confidence: 99%
See 1 more Smart Citation
“…These natural products have been reported to be safe, efficacious, biocompatible, and cost-effective alternatives to treat inflammatory diseases in folk medicine [38,14]. [39] has reported that several substances of plant origin such as flavonoids, saponins and tannins, are potential therapeutic agents in inhibiting or even decreasing inflammatory activity. An earlier study had shown that the presence of these phytochemicals, may be responsible for the anti-inflammatory activities demonstrated by the ethanol leaf extract of Sphenocentrum jollyanum [40].…”
Section: Discussionmentioning
confidence: 99%